Mannheimia haemolytica and Bibersteinia trehalosi serotypes isolated from lambs with ovine respiratory complex in Spain - GONZALEZ, J. M.; LACASTA, D.; FERRER, L. M.; FIGUERAS, L.; ABADIE, G.; DE LAS HERAS, M. (Journal of the Hellenic Veterinary Medical Society, 2017)
Ovine respiratory complex causes significant economic losses in ovine production systems around the world. Mannhemia haemolytica and Bibersteinia trehalosi are the two most frequently isolated bacterial species. In this study, bacterial isolates of M. haemolytica and B. trehalosi isolated from dead lambs were serotyped by means of indirect haemagglutination, with the general aim to improve information in the preparation for candidate strains for relevant vaccines. In total, 84 isolates were serotyped. Eight different M. haemolytica serotypes and four different B. trehalosi serotypes were identified. The most frequent M. haemolytica serotypes were A2 (29% of isolates), A12 (18%) and A1 (12%), while B. trehalosi were predominantly T4 (40% of isolates) and a group sharing characteristics of T3 and T15 serotypes (43%). Isolation of T4 serotype was associated with lack of consolidated lesions in lungs, whilst isolation of T3-T15 group was associated with lung consolidation. It is concluded that a potential vaccine to control the disease presented as a bacterin based on outer membrane proteins and leucotoxins of the organisms, it should contain the above, frequently implicated serotypes. Alternatively, vaccines based on iron-regulated proteins can be possible replacements.